Negative symptoms in schizophrenia differ across environmental contexts in daily life. (May 2023) - Luther, Lauren; Raugh, Ian M.; Collins, Delaney E.; Knippenberg, Anna R.; Strauss, Gregory P.
Abstract: A recent environmental theory of negative symptoms posits that environmental contexts (e.g., location, social partner) play a significant—yet often unaccounted for—role in negative symptoms of schizophrenia (SZ). "Gold-standard" clinical rating scales offer limited precision for evaluating how contexts impact symptoms. To overcome some of these limitations, Ecological Momentary Assessment (EMA) was used to determine whether there were state fluctuations in experiential negative symptoms (anhedonia, avolition, and asociality) in SZ across contexts (locations, activities, social interaction partner, social interaction method). Outpatients with SZ (n = 52) and healthy controls (CN: n = 55) completed 8 daily EMA surveys for 6 days assessing negative symptom domains (anhedonia, avolition, and asociality) and contexts. Multilevel modeling demonstrated that negative symptoms varied across location, activity, social interaction partner, and social interaction method. For the majority of contexts, SZ and CN did not report significantly different levels of negative symptoms, with SZ only reporting higher negative symptoms than CN while eating, resting, interacting with a significant other, or being at home. Further, there were several contexts where negative symptoms were similarly reduced (e.g., recreation, most social interactions) or elevated (e.g., using the computer, working, running errands) in each group. Results demonstrate that experiential negative symptoms dynamically change across contexts in SZ. Some contexts may "normalize" experiential negative symptoms in SZ, while other contexts, notably some used to promote functional recovery, may increase experiential negative symptoms.